Bad Faith in Trademark Registration: A Comparative Analysis of EU and Chinese Trademark Law - Zhang,Zhen (2024)
The thesis compares the differences between the European Union and China in terms of legal regulation of bad faith in trademark registration. The study aims to provide a detailed comparison of the similarities and differences between the two in legislative and judicial handling of trademark bad faith behavior. Additionally, the thesis addresses the challenges faced by the two jurisdictions in the administrative review and judicial adjudication of bad faith trademark behavior and proposes recommendations based on the advantages of both sides in dealing with such behavior. The thesis is divided into five chapters. Chapter One introduces the background of the study, emphasizing that in recent years, both the European Union and China have strengthened their supervision of bad faith trademark registration, and outlines the research purpose and methodology. Chapter Two compares the differences between the European Union and China in the definition, types, and legislation of bad faith trademark, emphasizing the necessity of regulating bad faith behavior. Chapter Three focuses on com-paring the criteria for judicial determination of bad faith trademarks in the European Union and China. Chapter Four summarizes the similarities and differences in the legal regulation of bad faith trademarks between the two jurisdictions and proposes recommendations. Chapter Five presents the final concluding remarks. Through this comprehensive comparative study, the thesis attempts to contribute to the advancement of knowledge in the field of trademark law and provides new insights for improving legislation and practices regarding bad faith trademark registration in both the European Union and China.
Keywords: Bad Faith Trademark Registration；EU Trademark Regulation；Chinese Trademark Law； Comparative Legal Study